Incidence, Risk Factors, and Complications Associated With In-Hospital Mortality in Emergency Surgery at Ramathibodi Hospital: A Retrospective Study - Nichawan Wirachpisit (2022)
Background: Previous studies have identified several risk factors associated with anesthesia and emergency surgery. However, there are no precise data for emergency surgery in Ramathibodi Hospital. Objective: To identify the incidence and risk factors associated with in-hospital mortality and perioperative complications in patients undergoing emergency surgery at Ramathibodi Hospital. Methods: This was a retrospective study of all patients undergoing emergency surgery at Ramathibodi Hospital from June 2014 to May 2015. Data collected included sex, age, American Society of Anesthesiologists (ASA) classification, comorbidities, type and duration of surgical procedures and period during which it was performed, and major complications. Statistical analysis was performed to determine the differences between groups with the significant level at P < 0.05. Results: A total of 3520 patients underwent emergency surgery. In-hospital mortality and perioperative complication rate were 0.68% and 22.81%, respectively. Several risk factors associated with intraoperative complications such as extreme age < 1 year (odds ratio [OR], 3.56; 95% CI, 1.6 - 7.93); ASA classification > II (OR, 16.76; 95% CI, 10.05 - 27.94); cardiovascular/thoracic surgery (OR, 5.91; 95% CI, 3.29 - 10.61); pediatric surgery (OR, 7.62; 95% CI, 3.38 - 17.17); respiratory comorbidities (OR, 4.37; 95% CI, 3.43 - 5.58); sepsis (OR, 6.21; 95% CI, 4.06 - 9.49); and post cardiac arrest (OR, 9.29; 95% CI, 2.04 - 42.30). Conclusions: The incidence of in-hospital mortality and perioperative complications after emergency surgery were 0.68% and 22.81%, respectively. Several risk factors related to major complications should be aware by anesthesia providers.